Cervical spine and spinal cord trauma: Round table XXVII Uruguayan Congress of Surgery: coordinator Pedro Benedek - Benedek, Pedro; Bastarrica, Ernesto; Borsani, Jorge; de Tényi, Andrés; Lanterna, Washington; Lausarot, Miriam; Nin Vivo, Esteban; Nogueira, Alejandro; Rodríguez Juanotena, Jorge; Suero, Carlos (Cirugía del Uruguay, 1977)
Cervical spinal injuries are due to the exaggeration in time and space of normal movements for the age and biology of the traumatized person.